Internet of Things in Vehicle Safety – Obstacle Detection and Alert System (International Journal of Engineering and Computer Science, 2018)
Recent development of the Internet of Things (IoT) and Smart Things provides an opportunity for the informationization for the automotive industry. This article describes Obstacle Detection and Alert System (ODAS) both incorporated as a single system for the obstacles such as speed breakers, barricades on the road using Internet of Things. Obstacle detection system uses in-built algorithm to detect an obstacle on the road using minimal vehicle parameters such as vehicle speed, steering angle. Obstacles locations thus marked by the detection system are stored locally and uploaded to cloud from time-to-time. Cloud server processes data from different vehicles and finalizes that there is a real obstacle at the particular location based on its own algorithm. Obstacles locations thus confirmed by the cloud server are downloaded to obstacle alert system from time-to-time, which alerts the driver about the obstacle on the road when the driver is nearing the location of the obstacle. This system also provides option to see obstacles location super-imposed on google maps so that user can plan his efficient route in advance. Existing systems only have road sign indications for obstacles such as speed breakers, barricades which the driver might not notice during driving, especially at night times. Existing google maps data do not have option to find road obstacles such as speed breakers, barricades information on it. The system aims to overcome these short-comings by a dedicated system which provides audible and visual alert about road obstacles.